Media Bola Pancasila dengan Team Games Tournament dalam Mewujudkan Profil Pelajar Pancasila - Prastiyo, Fendika (Jurnal Didaktika Pendidikan Dasar, 2024)
Research problems include learning outcomes that are less than the minimum completion criteria (KKM), strengthening the concept of Pancasila values ​​which is still low, and learning that is less active, interactive and enjoyable. The aim of the research is to create active, interactive and fun learning and improve the learning outcomes of class VI students so that they achieve the KKM. Pancasila Ball (BOCA) is a learning prop that contains the values ​​of Pancasila Principles. The learning model uses Team Games Tournament (TGT). The research method is Classroom Action Research (PTK) with 3 cycles, pre-cycle, cycle-1 and cycle-2. Research techniques use observation, written tests, surveys, and reflection sheets. The research was carried out in class 6B with a total of 29 students (15 boys and 14 girls). Student completion results increased in each cycle, namely, Pre-cycle 1 child (3%), Cycle-1: 8 children (28%), and Cycle-2: 21 children (72%). The results of the research state that the use of BOCA in learning Pancasila Values ​​ ​​material for class VI SDN Panjang 2 can create active, interactive and fun learning and improve student learning outcomes by using Bola Pancasila Media (BOCA) with the Team Games Tournament (TGT) model.